The Y(4230) as a D1D molecule - von Detten Leon; Hanhart Christoph; Baru Vadim (EPJ Web of Conferences, 2024)
Abstract. We show that the currently available data are consistent with Y(4230) being a D1D¯ hadronic molecule. By a simultaneous fit to data from e+e− → D0D*−π+, J/ψπ+π−, J/ψK+ K−, hcπ+π−, J/ψη, χc0ω, χc1(3872)γ and µ+µ−, we demonstrate that this single state can explain the experimental signals in the mass range from 4.2 to 4.35 GeV.